2019
DOI: 10.1111/asj.13307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunocastration performed at two live weights on the growth physiology, temperament and testicular development of feral beef bulls

Abstract: The aim of this study was to examine the effect of administering an anti-gonadotropin-releasing hormone vaccine (Improvac ® , developed for pigs) on the performance, temperament, testicular development, and hormone and metabolite profiles of feral bulls (Bos taurus) vaccinated at two different live weights (LW). In all, 16 Serrana de Teruel animals were involved in this 2 x 2 factorial design using the factors LW (LIGHT vs. HEAVY) and vaccine treatment (control, C vs. vaccinated, VA). All animals received the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Additionally, the fAM concentrations were unable to explain the differences in temperament scores in the male common eland in the present study, suggesting that genetic and environmental factors have a larger influence on their response to handling than their androgen levels. Noya et al (2019) studied the influence of immunocastration on the temperament of feral bulls with different live weights, but immunocastration had no influence, which is in line with the outcome of the present study. Androgens positively influence muscle fibre hypertrophy, and thus the growth and development of animals, which makes male animals more muscular, but also potentially more aggressive (Price et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, the fAM concentrations were unable to explain the differences in temperament scores in the male common eland in the present study, suggesting that genetic and environmental factors have a larger influence on their response to handling than their androgen levels. Noya et al (2019) studied the influence of immunocastration on the temperament of feral bulls with different live weights, but immunocastration had no influence, which is in line with the outcome of the present study. Androgens positively influence muscle fibre hypertrophy, and thus the growth and development of animals, which makes male animals more muscular, but also potentially more aggressive (Price et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Such attributes give male animals the opportunity to defend themselves, and to strive to surpass conspecifics in a social group by increasing their social rank (Pelletier and Festa-Bianchet, 2006), but this also makes them easily reactive to novel objects, due to their tendency for excitable temperaments. Noya et al (2019) also suggested that the inability of immunocastration to influence temperament might be related to other factors other than decreased androgen production, such as genetics and environment. Like other social animals, common eland are sensitive to their environment, and learn to improve their chance of survival by adjusting their behaviour through postural lateralization and ritualization (Kiley-Worthington, 1978;Wirtu et al, 2005;Bordes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between studies could be influenced by the age at which animals are castrated. Older animals are more susceptible to significant weight loss and stress, as suggested by Noya, Ripoll, Casasús, and Sanz [ 41 ]. In agreement with Amatayakul-Chantler et al [ 5 ], the greater final LW of immunocastrated bulls in this study seems to corroborate the advantages of immunocastration over surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A series of complex biological processes occurred after immunocastration in animals, including retardation of testicular development, hormonal secretion, and spermatogenesis [ 18 ]. So far, previous studies have primarily focused on investigating changes in genes and pathways in the testes after testosterone deficiency in rodents [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%